(untitled) (Sains Humanika, 2017)
The effort of the Ministry of Education of Malaysia (KPM) in strengthening Science, Technology, Engineering and Mathematics (STEM) educations in Malaysia is to increase the source of experts and skilled workforce in the field of research and industry. The inspiration of KPM to empower the strengthening of STEM can be implemented with the availability of ICT. ICT can be a comprehensive tool in teaching and facilitation (PdPc) of science that is complete and inclusive. ICT based science learning is an outcome of the combination of principle and strategy within education and technology domains. ICT has a great potential to spur the learning process and extensive thinking skill among the students since they regularly incorporate the use of ICT in their daily life. However, this mentioned potential has not been fully disclosed in Malaysia. Countries like Finland has a ‘road map’, meanwhile Canada has a framework for T&L of science based on ICT. Malaysia still has not developed a ‘road map’ or a framework as the above for science especially in SJK(T). Besides that, poor achievement in science education is becoming a continuous issue in SJK (T). This case is proven to be true when the results for science subject among the SJK (T) UPSR candidates are dropping since the year 2011. Hence, various elements involving the expansion of ICT based teaching and facilitation of science framework guideline should be identified in Malaysia. The framework guideline will be built based on the Malaysian culture which has the potential to spur success and science competency at the international level.